The Use of Language Games in Enhancing English Vocabulary Mastery of Fourth-Grade Elementary School Students at Sultan Iskandar Muda - Nurhaliza Putri Cantika Wijaya; Nazli Fahada; Ahmad Fuadi (Education Achievement: Journal of Science and Research, 2026)
Vocabulary mastery is essential in English learning, especially for elementary students in EFL contexts. However, many learners face difficulties in understanding, retaining, and using vocabulary due to conventional teaching methods that rely heavily on memorization. This study aimed to evaluate the effectiveness of language games in improving students’ vocabulary mastery, identify the most effective types of games, and analyze their impact on motivation and classroom participation. The research used Classroom Action Research (CAR) based on the Kemmis and McTaggart model, involving planning, action, observation, and reflection. It was conducted at SD Sultan Iskandar Muda with 40 fourth-grade students. Data were collected through pre-tests and post-tests, observations, interviews, and documentation, and analyzed using both quantitative and qualitative approaches. The results showed significant improvement in vocabulary achievement, with mean scores increasing from 58.4 (pre-test) to 68.7 (Cycle I) and 82.3 (Cycle II). The percentage of students achieving the Minimum Mastery Criteria (KKM) rose from 30% to 55% and then 85%. Qualitative findings revealed that games such as word matching, memory cards, guessing games, and role-play effectively enhanced vocabulary retention, motivation, participation, and students’ confidence in learning.